A Comparative Study on Hulled Adlay and Unhulled Adlay through Evaluation of Their LPS‐Induced Anti‐Inflammatory Effects, and Isolation of Pure Compounds. Issue 3 (March 2015) - Choi, Goeun; Han, Ah‐Reum; Lee, Joo Hee; Park, Ji‐Youn; Kang, Unwoo; Hong, Jongki; Kim, Yeong Shik; Seo, Eun‐Kyoung
Abstract Coicis semen (=the hulled seed of Coix lacryma‐jobi L. var. ma‐yuen (Rom.Caill.) Stapf; Gramineae), commonly known as adlay and Job's tears, is widely used in traditional medicine and as a nutritious food. Bioassay‐guided fractionation of the AcOEt fraction of unhulled adlays, using measurement of nitric oxide (NO) production on lipopolysaccharide (LPS)‐stimulated RAW 264.7 macrophage cells, led to the isolation and identification of two new stereoisomers, (+)‐(7′S, 8′R, 7″S, 8″R)‐guaiacylglycerol β‐O‐4′‐dihydrodisinapyl ether (1) and (+)‐(7′S, 8′R, 7″R, 8″R)‐guaiacylglycerol β‐O‐4′‐dihydrodisinapyl ether (2), together with six known compounds, 3–8. Compounds 3 and 4 exhibited inhibitory activities on LPS‐induced NO production with IC50 values of 1.4 and 3.7 μM, respectively, and suppressed inducible nitric oxide synthase (iNOS) and cyclooxygenase‐2 (COX‐2) protein expressions in RAW 264.7 macrophage cells. Simple high‐performance liquid chromatography with ultraviolet detection (HPLC/UV) was used to compare the AcOEt fraction of unhulled adlays responsible for the anti‐inflammatory activity in RAW 264.7 cells and the inactive AcOEt fraction of hulled adlays.